Qualidade da água de chuva armazenada em cisternas de placas e de polietileno no semiárido do Estado da Paraíba - Machado, Taysa Tamara Viana (2017)
Rainwater has been increasingly used to reduce the number of people without access to water for consumption. Government programs for the installation of cisterns for the storage and use of rainwater by rural zone residents of the Brazilian semiarid region have been successful since its inception at the beginning of this century. However, there are not enough amounts of studies on quality assurance for human consumption available in the specialized literature. Thus, the objective of the research reported in this thesis is to analyze the rainwater stored in concrete and polyethylene cisterns which are intended to the supply of diffuse populations of the semiarid state of Paraíba - Brazil. The highlights of this work are the problems of water quality reflected by the different rainfall in the catchment areas, the quality standards meeting according to the regulations, and the differences between the water stored in concrete and polyethylene cisterns, as a consequence of the type of its constituent material. The methodology used included the collection of water samples in the municipalities of Cabaceiras and São Sebastião de Lagoa de Roça. The data concerning the parameters of the water quality were obtained through measurements using multiparameter probe and laboratory analysis. The results were submitted to statistical analysis, using tests to compare the physical and chemical parameters of the water, rejecting or not the hypothesis of the samples coming from the same population, according to the objectives, and the verification of result conformity of the parameters of water quality with the Ministry of Health Ordinance No. 2.914/2011 for water intended for human supply. The results indicated the rejection of the two formulated hypotheses, translated in the absence of differences between the representative parameters of the water quality in the two types of cisterns, and also between the cisterns with catchment areas in regions of different rainfalls. As for the verification of conformity, it was concluded that it occurred in the great majority of the physical and chemical parameters of the analyzed list. In the microbiological analyzes performed, Escherichia coli was absent and the total coliforms were present in all water samples, then it was concluded that there was not a compliance with the Ordinance regarding the microbiological parameters; therefore, there was an agreement with the results of other researchers, indicating the need for simple water treatment before human consumption.